Microemulsification of clove essential oil improves its in vitro and in vivo control of Penicillium digitatum. (July 2016) - He, Shoukui; Ren, Xiaoyun; Lu, Yangfan; Zhang, Yunbin; Wang, Yifei; Sun, Linjun
Abstract: Clove essential oil (CEO) is a promising alternative to chemical fungicides for postharvest decay control. However, relatively high concentrations required for in vivo microbial growth inhibition limit its application. Hence, this study aimed to strengthen the antifungal activity of CEO by loading it in microemulsion system. Two CEO microemulsions (ME-1, CEO/ethanol/Tween 80 = 1:2:7; ME-2, CEO/ethanol/Tween 80 = 1:3:6) were evaluated their antifungal activity against Penicillium digitatum in vitro and in navel oranges. Microemulsification of CEO caused a reduction of MIC (minimum inhibitory concentration) from 0.50 μl/ml to 0.25 μl/ml, while the MFC (minimum fungicidal concentration) remained unchanged at 0.50 μl/ml, indicating enhancement of only fungistatic activity. The decay incidence of navel oranges treated with ME-1 and ME-2 was significantly ( p < 0.05) reduced by 34.51% and 20.93%, respectively, in comparison to that of pure oil treatment after 5 days' storage at 25 °C. In the vapor phase, CEO microemulsions had the best control of lesion diameter and decay development. Additionally, the improved antifungal activity of CEO microemulsions may be related to their stronger ability to suppress spore germination and germ tube elongation of P . digitatum . The enhanced control of postharvest green mold of navel oranges by CEO after microemulsification can broaden its application in food industry. Highlights: Two clove essential oil (CEO) microemulsions were formulated. Microemulsions showed enhanced fungistatic activity against P . digitatum . Microemulsion and its vapor controlled postharvest green mould of navel oranges. Microemulsions decreased spore germination and germ tube elongation of P . digitatum .